The Role of OECD in the Issuance of Indonesia’s Personal Data Protection Law: A Norm Localization Approach - -, Wulandari (Hasanuddin Journal of International Affairs, 2026)
With the increase in digital technologies adoption, governments are expected to balance the dual objectives of securing national interests and upholding citizens' rights to personal data protection. In Indonesia, data governance has traditionally followed a state-centric model, as portrayed in the Electronic Information and Transactions (EIT) Law in 2008. However, a notable shift occurred in 2022 with the enactment of the Personal Data Protection Law, signalling Indonesia’s transition toward a more people-centric approach to data governance. It raises a question, why Indonesia changes its perspective from state centric to people centric approach in data governance? The author argues that OECD has taken a big role in this changing perspective. This research aims to examine the influence of OECD as a multilateral organization by great powers in shaping perspectives on data governance in Indonesia. Norm localization theory by Acharya (2009) suggests that success in this localization process depends on credible local actors and institutional compatibility. In Indonesia’s case, Airlangga Hartarto and the Coordinating Ministry for Economic Affairs fulfilled that role, negotiating national legitimacy and local constraints while translating the OECD’s liberal and open data governance agenda into tangible legal reform. Also, Indonesia’s Presidency in G20 as well as data breach and cyber-incident during IMEI registration procedure since 2020 help accelerate the issuance of Personal Data Protection Law. By combining OECD normative influence with a domestic elite predisposed to liberalization, the adoption of the Personal Data Protection Law is more than mere policy transfer. It represents norm localization, where imported norms are reinterpreted, adapted, and entrenched into Indonesia's legal system.